Employees' Perception of Human Aspects in TQM at GCC Standardization Organization - AlGhunaimi, Hisham; Awashreh, Raed (Journal of Ecohumanism, 2024)
The Gulf Standardization Organization (GSO), serving as the standardization body for the Gulf Cooperation Council (GCC) member states, has operated as a multinational entity across six Arabian Gulf countries for five years. Its primary functions include supervising and issuing Gulf Standards while endeavoring to enhance the quality infrastructure within the GCC nations. Despite its significant international engagements with organizations such as ISO and BSI, the awareness of its employees regarding its relationship with Total Quality Management (TQM) remains uncertain. To address this gap, this project aims to assess employees' familiarity with and awareness of the "soft" side of TQM and its implementation within the GSO. In-depth interviews were conducted with managerial, supervisory, and operational level employees to gather insights. The study reveals that while some employees have a basic understanding of TQM and its practices, the majority exhibit a limited awareness of its "soft" aspects. In light of these findings, the study recommends the GSO undertake a specialized qualitative inquiry into TQM and its "soft" side. This investigation elucidates the factors contributing to employees' lack of awareness, empowerment deficiencies, and delays in TQM implementation. By identifying these weaknesses, the GSO can develop tailored training programs and promptly integrate TQM principles to enhance organizational effectiveness.